Mechanical and Metallographic Effects of Laser Hardening of Two AHSS Steels - Amorim, M. S.; Neves, D.; Azevedo Silva, F. de [UNESP] (Amer Soc Testing Materials, 2016)
The search for suitable materials for the transport industry, to meet more stringent regulations related to crashworthiness, emissions, and fuel economy led to the development of advanced high-strength steels (AHSS). Thermal treatments, for example, using lasers as a process tool, can locally improve some characteristics of these materials like plastic deformation capability. The high energetic efficiency of a laser process, and its capability to be automated, are some of the advantages of using such a process. This study aims to investigate the effects of local heat treatment (involving changes in the solid state), by laser radiation, in the mechanical properties and microstructures of two types of advanced high-strength steels, the dual-phase DP 600, and the transformation-induced plasticity TRIP 750. A method to evaluate the interaction between laser radiation and the materials is proposed. Previous studies in this area focused, basically, in welding or cutting technology, and for the modern TRIP steel studied here, there is a scarcity of published material regarding laser-material interaction. Hardness and tensile tests revealed, for the range of process parameters studied, an improvement (up to 30 % with relation to the base material) in yield strength and ultimate strength (up to 15 %). Revealed also is a dramatic reduction in the elongation (up to 80 %) for both materials. Optical metallography analysis revealed that the resulting microstructures presented grain refinement and formation of lath martensite according to the level of laser absorption, improving up to twice the original hardness.
Keywords: advanced high-strength steels; local heat treatment; laser materials processing; materials characterization; dual-phase steel; TRIP steel